Pengaruh Model Problem Based Learning (PBL) terhadap Hasil Belajar Matematika Kelas VII SMP Negeri 1 Sidua Ori - Temazisokhi Ndruru (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
Student learning outcomes are the output of the teaching and learning process. One of the problems in learning at school is the low student learning outcomes. This can be seen from the initial data on students' daily test scores which are still below the KKM. Many factors influence learning outcomes, one of which is the learning model. The Problem Based Learning (PBL) learning model is a cooperative learning model that requires students to be active and motivate students so that they can support and help each other in mastering the subject matter being studied. The aim of this research is to determine the differences in Mathematics learning outcomes between those using the PBL learning model and the conventional learning model for class VII students at SMP NEGERI 1 SIDUA ORI. This research is experimental research with a pretest-posttest design. The subjects in this research were students in class VII_A as experimental class I and class VII_B as experimental class II, with data processing techniques using a two-way t-test. After the research was carried out, it turned out that the learning outcomes in classes that used the PBL learning model were 81.14 higher than in classes that used the conventional learning model, 76.98. Based on statistical tests, tcount is 2.4046 and ttable is 1.9893. Because the value of tcount > ttable (2.4046 > 1.9893) means that it can be concluded that Ho is rejected and Ha is accepted. From the analysis that has been carried out, it can be concluded that there is a significant difference between Mathematics learning outcomes using the PBL learning model and the conventional learning model for class VII students at SMP Negeri 1 Sidua Ori.